1987
DOI: 10.1152/jn.1987.58.2.404
|View full text |Cite
|
Sign up to set email alerts
|

Activity-evoked increases in extracellular potassium modulate presynaptic excitability in the CA1 region of the hippocampus

Abstract: 1. The effects of stimulus-evoked potassium release on the excitability of presynaptic axons were studied in the rat hippocampal slice preparation. Extracellular stimulation and recording in the stratum radiatum of CA1 yielded a characteristic field potential corresponding to the compound action potential of nonmyelinated afferents and subsequent postsynaptic activation of pyramidal cells. 2. Repetitive stimulation (1 s; 2-100 Hz) produced biphasic changes in the excitability of the afferents. Initial response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
109
2

Year Published

1989
1989
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(116 citation statements)
references
References 30 publications
5
109
2
Order By: Relevance
“…Thus, the velocity of ephaptic propagation will increase at an increased K + concentration. In contrast, the conduction velocity of nerve fibres may decrease (Poolos et al 1987).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Thus, the velocity of ephaptic propagation will increase at an increased K + concentration. In contrast, the conduction velocity of nerve fibres may decrease (Poolos et al 1987).…”
Section: Discussionmentioning
confidence: 94%
“…However, these velocities may differ somewhat in the epileptogenic slice where the extracellular K § concentration is increased (Heinemann et al 1977;Somjen and Giacchino 1985;Heinemann 1987). Poolos et al (1987) reported a decrease in propagation velocity of fibres in the stratum radiatum of CA1 by~ 30% at an increase of the interstitial K § concentration from 3 to 9 mM. If there is any effect of extracellular K § on the propagation velocity of fibres in the epileptogenic slice, it will be a decrease.…”
Section: Discussionmentioning
confidence: 98%
“…The synaptically-evoked glial membrane depolarization is a direct measure of the extracellular potassium rise 8 , due in part to presynaptic action potential firing, but mostly to postsynaptic depolarization 7 . Therefore recordings of glial membrane potential dynamics can be used to investigate modifications in presynaptic excitability, postsynaptic activity, extracellular space volume and potassium buffering capacities 6,8 .…”
Section: Discussionmentioning
confidence: 99%
“…To visualize the extent of the gap-junction mediated astroglial networks, dye-coupling experiments should be performed in current clamp mode, without any current injection, to enable passive diffusion of low molecular dyes (< 1.5 kDa), such as sulforhodamine-B, through gap . The majority of the slow inward current reflects potassium entry into the astrocyte following postsynaptic depolarization, since it is also abolished by kynurenic acid, which inhibits postsynaptic ionotropic glutamate receptor activity ( Figure 2B and Figure 2C 1 ) [3][4][5][6] , known to represent the main source (80 %) of potassium release 7 . The remaining rapidly rising and decaying inward current is inhibited by the GLT antagonist DL-TBOA (light grey trace, Figure 2B and Figure 2C 2 ).…”
mentioning
confidence: 99%
“…The Na + /K + pump is activated and the concentration of extracellular potassium decreases at a greater rate around the thin branch 82 . Accumulation of extracellular potassium has also been observed in the olfactory nerve 90 and in hippocampal axons 91 , and could be the origin of unreliable conduction. Propagation failures that are induced by repetitive stimulation might also result from hyperpolarization of OUABAIN Extracted from the seed of the Strophantus, a tropical creeper, ouabain is a cardiotonic that blocks sodium channel electrogenic pumps.…”
Section: Geometrical Factors: Branch Points and Swellingsmentioning
confidence: 99%